Architectural Interventions and Urban Transformation in the Arrangement of Mevlana Celaleddýn Rumý Square Ignoring Ontological Planning Approach - Havva Alkan Bala; Ahmet Alkan (European Regional Science Association (ERSA), 2014)
If urban design decisions are taken ignoring the historical value of buildings, cultural inputs and meaning of the space based on memories and experiences, the sense of place disappears like in Konya Mevlana Celaleddin Rumi Square. Konya was the capital of Anatolian Seljuk, and the Mevlana Celaleddin Tomb, which is the symbol of the city. The aim of this study is to try to understand the architectural interventions and urban transformation within Konya Mevlana Celaleddin Rumi Square that has the potential of producing creating general results. Ontological Planning approach is adding spirit to the space and also addition of the morphological energy of the space to urban planning. Ignoring ontological planning approach, all spatial decisions for making better will create new problems and will create worse. Today, Mevlana Museum and the area in front of the museum has arranged to a square which will serve to tourism, to political purposes since it is the prestige venue and space of the city. Mevlana wants to be visited, not want to change to a political area. The Mevlana Celaleddin Rumi Museum and surrounding arrangements have environmental, cultural, social and symbolic values of urban and that is expected to be a landmark associated with beliefs and also remained loyal to the cultural sense and historical texture. Design which ignore the most basic facts of doctrine and hosting irregularity to the principle of square arrangement and the spirit of the Mevlana was offered to the public as a new urban arrangement. The new design arrangements is a large and covered rough ground square for 35,000 person, abandoned by people and birds, without trees. Sufism has spread to three continents and the green Kubbe-i Hadra of Celaleddin Rumi in Konya regarded as the center of its. Design decisions and spatial arrangements which are not enough discussed by experts and which are taken quickly decisions for the world heritage site should be questioned and discussed from the beginning. This study is the beginning of inquiry on the context of scientific field
Keywords: 330; Urban Transformation; Square; Mevlana Celaleddin Rumi; Sense of Place; Sufism; Ontological Planning Approach